FORMULASI SEDIAAN ANTIOKSIDAN FACIAL WASH EKSTRAK METANOL DAUN GANITRI (Elaeocarpus ganitrus Roxb.) DENGAN VARIASI SODIUM LAURIL SULFAT SEBAGAI SURFAKTAN - Evi Marlina; Naelaz Zukhruf Wakhidatul Kiromah; Titi Pudji Rahayu (Jurnal Ilmiah Manuntung: Sains Farmasi Dan Kesehatan, 2022)
Ganitri leaves (Elaeocarpus ganitrus Roxb.) contain flavonoid compounds that function as antioxidants. Antioxidants in cosmetics are used to prevent skin damage due to exposure to free radicals. Facial Wash is a cosmetic preparation to help remove dead skin cells, rejuvenate the skin, remove dirt, oil and provide moisture. This study aims to obtain a facial wash formula that has good characteristics and is effective as an antioxidant by varying the concentration of sodium lauryl sulfate, namely F1 (0.25%), F2 (0.5%) and F3 (1%) as surfactant. The results showed that variations in SLS concentration had a significant effect on the physical evaluation of the preparation with a p value of <0.05. Formula 3 (SLS 1%) provides the best facial wash characteristics with the results of the test parameters meeting the standards. The results of the antioxidant activity test showed that formula 3 had an IC50 value of 17.36 ppm which was categorized as very strong with ascorbic acid as a comparison of 10.70 ppm and a negative control of 54.11 ppm.